Towards a framework for improving cyber security resilience of critical infrastructure against cyber threats : a dynamic capabilities approach - Järveläinen, Jonna; Dang, Duong; Mekkanen, Mike; Vartiainen, Tero (Taylor & Francis, 2025)
Interruptions in critical infrastructures (CIs) such as energy grids, telecommunication networks, or transportation can have severe and lasting impacts on societies. CIs are vulnerable to disruptions like cyberattacks, necessitating enhanced resiliency. This conceptual paper focuses on ensuring CI resiliency with dynamic capabilities, which have been previously applied mainly in organisational resiliency literature. On the operational level, when a disruption event happens, we explore the use of an AI-enabled tool and collective mindfulness processes and consider them essential in sensing, seizing, and transforming the organisation. However, when the organisation learns, these response practices facilitate transforming the organisation on a strategic level. Two cases are used to illustrate the conceptual framework idea.
Keywords: Critical infrastructure; dynamic capabilities; artificial intelligence tools; collective mindfulness; resilience; fi=Tietojärjestelmätiede|en=Information Systems|